2001
DOI: 10.1016/s0002-9440(10)61785-3
|View full text |Cite
|
Sign up to set email alerts
|

The Inner Ear of Dogs with X-Linked Nephritis Provides Clues to the Pathogenesis of Hearing Loss in X-Linked Alport Syndrome

Abstract: Alport syndrome is an inherited disorder of type IV collagen with progressive nephropathy, ocular abnormalities, and high-tone sensorineural deafness. In X-linked Alport syndrome, mutations in the COL4A5 gene encoding the ␣5 chain of type IV collagen lead to loss of the ␣3/␣4/␣5 network and increased susceptibility of the glomerular basement membrane to long-term damage. The molecular defects that underlie the otopathology in this disease remain poorly understood. We used a canine model of X-linked Alport synd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
26
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 47 publications
0
26
0
Order By: Relevance
“…The inner ear phenotypes of mice and dogs with Alport-like type IV collagen mutations have been described in detail. 17,18 Currently, two main classes of collagen-binding receptors are known: the integrins, which are heterodimers formed between b1 and a1, -2, -10, or -11 subunits, and the Discoidin domain receptors (DDRs). 19 The mammalian genome contains two DDR genes, DDR1 (previously also known as NEP, Cak, TrkE, MCK-10, EDDR, or NTRK4) and DDR2 (CCK-2, Tyro10, or TKT).…”
mentioning
confidence: 99%
“…The inner ear phenotypes of mice and dogs with Alport-like type IV collagen mutations have been described in detail. 17,18 Currently, two main classes of collagen-binding receptors are known: the integrins, which are heterodimers formed between b1 and a1, -2, -10, or -11 subunits, and the Discoidin domain receptors (DDRs). 19 The mammalian genome contains two DDR genes, DDR1 (previously also known as NEP, Cak, TrkE, MCK-10, EDDR, or NTRK4) and DDR2 (CCK-2, Tyro10, or TKT).…”
mentioning
confidence: 99%
“…In the murine and canine inner ear, only the ␣1/␣2 network is present at birth, with the ␣3/␣4/␣5 network not detected until around 2 weeks in mice 14 and 3 to 4 weeks in dogs. 15 The ␣1/␣2/␣5/␣6 network is not expressed in this site except in vascular smooth muscle.…”
Section: Discussionmentioning
confidence: 96%
“…They allowed the understanding of normal hearing at molecular level and the mechanisms that are affected when there is one specific mutation 22 . Investigations in Knockout COL4A3 rats suggested affections to stria vascularis as the cause of hearing loss in AS 18 and in Samoyed dog, inner ear spiral ligament may be responsible for SNHL in low sounds 19 . Studies in human ears in patients with AS are restricted because of difficulties to reach the temporal bones, the limited number of studied pieces, difficulties to fix and the process of autolysis after death, contributing to the differences observed in the descriptions of these temporal bones in the literature 16 .…”
Section: Discussionmentioning
confidence: 98%
“…Thinning of basal membrane along the basilar membrane may have some effect on the rigidity of the membrane and affections to stria vascularis may restrict the blood flow through the metabolically hyperactive tissue 18 . Studies in dogs Samoyed (X-linked animal model of AS) demonstrated absence of chains a3, a4 and a5 in spiral ligament 19 . The absence of these chains in the region could result in reduced capacity of myofibroblasts to maintain enough tension in the basilar membrane, with loss of perception for high sounds.…”
Section: Animal Studiesmentioning
confidence: 99%
See 1 more Smart Citation